Cloud Gaming: uma revisão da literatura - Vicente, M. (2021)
Cloud Gaming is an internet service, which allows the customer to play a video game on any device through the cloud. The main objective of this type of service is to provide players with an immediate gaming experience on any device, without needing to have potent hardware to run it. Despite being a recent service and still underpowered, it brings advantages and opportunities for the Gaming Industry. This article aims to define the historical evolution of technology associated with games, the pioneer companies and those that currently present themselves as references in terms of sales volume in this market and identify opportunities and challenges in the development and implementation of Cloud Gaming Services in the Gaming Industry, so that companies can expand. This article aims to arouse the interest of researchers in the areas of Cloud Computing for this gaming market. Cloud Gaming é um serviço de internet que permite ao cliente jogar um videojogo em qualquer dispositivo através da cloud. O principal objetivo deste tipo de serviço é fornecer aos jogadores uma experiência imediata dos jogos em qualquer dispositivo, sem necessitar de ter hardware potente para executá-los. Sendo um serviço recente e pouco potencializado, traz vantagens e oportunidades para a Indústria de Gaming. O presente artigo tem como objetivos descrever a evolução histórica da tecnologia associada aos jogos, as empresas pioneiras e as que atualmente se apresentam como referências em termos de volume de vendas neste mercado e identificar oportunidades e desafios no desenvolvimento e implementação dos Serviços de Cloud Gaming na Indústria de Gaming, de forma que as empresas se possam expandir. Este artigo pretende despertar o interesse dos investigadores das áreas de Cloud Computing para este mercado de jogos.